Rate of convergence of beta operators of second kind for functions with derivatives of bounded variation - Vijay Gupta (International Journal of Mathematics and Mathematical Sciences, 2005)
We study the approximation properties of beta operators of second kind. We obtain the rate of convergence of these operators for absolutely continuous functions having a derivative equivalent to a function of bounded variation.